Preparation of caffeic acid grafted chitosan self-assembled micelles to enhance oral bioavailability and antibacterial activity of quercetin - Ren, Xin; Ren, Juan; Li, Yipeng; Yuan, Sikun; Wang, Gengnan (Frontiers in Veterinary Science, 2023)
Quercetin (QR) is a naturally occurring flavonoid organic compound that has poor solubility in water and highly unstable in alkaline conditions, resulting in limited absorption in poultry.Consequently, in our experiment, QR was employed as a model compound, encapsulated within the caffeic acid graft chitosan copolymer (CA-g-CS) self-assembled micelles to enhance its solubility, stability and exhibit a synergistic antibacterial effect. The optimization of the formula was carried out using a combination of single-factor experimentation and the response surface method. The in vitro release rate and stability of CA-g-CS-loaded QR micelles (CA-g-CS/QR) in various pH media were studied and the pharmacokinetics in white feather broiler chickens was evaluated in vivo.Additionally, the antibacterial activity was investigated using Escherichia coliCMCC44102 and Escherichia coli of chicken origin as the test strain. The results showed the optimized formula for the self-assembled micelles were 4 mL water, 0.02 mg/mL graft copolymer, and 1 mg QR, stirring at room temperature. The encapsulation efficiency was 72.09%. The resulting CA-g-CS/QR was uniform in size with an average diameter of 375.6±5.9 nm. The release pattern was consistent with the Ritger-Peppas model. CA-g-CS/QR also significantly improved the stability of QR in alkaline condition. The relative bioavailability of CA-g-CS/QR was found to be 1.67-fold that of the reference drug, indicating a substantial increase in the absorption of QR in the broiler. Compared to the original drug, the antibacterial activity of CA-g-CS/QR was significantly enhanced, as evidenced by a reduction of half in the MIC and MBC values. These results suggest that CA-g-CS/QR improves the bioavailability and antibacterial activity of QR, making it a promising candidate for clinical use.